UPAYA PERBAIKAN GIZI 1000 HARI PERTAMA KEHIDUPAN DALAM RANGKA PENCEGAHAN STUNTING BALITA MELALUI OPTIMALISASI PERAN TENAGA GIZI DI KABUPATEN BANYUMAS - Kusumawati, Erna; Rahardjo, Setiyowati; Permata Sari, Hesti (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2016)
ABSTRACTThe first period of 1,000 days of life is a sensitive period due to the impact of the baby during this period. It will be permanent and can not be corrected. One of effort to prevent stunting is provide nutrition services in health centers by using surveillance stunting. The method used participatory by involving partners to play an active role in the activities and accompanied by a team act as a resource and facilitator. The data analysis useddependentt-test measured by changes in pretest and posttest scores. There are 80 % diploma of nutrition, most of them (60%) have 5 years work experience. There was an increased knowledge before and after training is of 9.63 to 9.94, but there was no significant differences in knowledge before and after training p=0,078 (>0.05). For the training, there was an increased skills before and after the training (3.66 to 6.09), p= 0.000 (<0 , 05), it mean that there was significant differences in the skills before and after the intervention. In order stunting surveillance program is expected to involve the health department for nutritionist and midwife to monitor nutrition tracking and reporting activities, especially stunting routine.Keywords : Stunting, Nutritionist, Surveilans Kesmasindo, Volume 8(2) Juli 2016, Hal. 90-98